Letter Bishopshire, Kent, to Walter B. Rodd, Roseville, NSW - Conrad, Joseph, 1857-1924. (1924)
Describes his visits to Australia in 1878, 1880, 1887 and 1892-1893 during his seafaring days.
Manuscript reference no.: NLA MS 8807.
Polish novelist who lived in England.
Keywords: Rodd, Walter B. -- Correspondence; Conrad, Joseph, -- 1857-1924 -- Correspondence; Novelists, English -- 20th century -- Correspondence; Australia -- Description and travel -- 1851-1900.; Novelists